Wati (Piper methysticum) medicinal plant: The ethnobiological and ethnomedicinal values of the Marind tribe in Merauke, Papua, Indonesia - SUHARNO SUHARNO; ROSYE HEFMY RECHNELTY TANJUNG; SUPENI SUFAATI; VERENA AGUSTINI (Biodiversitas Journal of Biological Diversity, 2016)
Suharno, Tanjung RHR, Sufaati S, Agustini V. 2016. Wati (Piper methysticum L.) medicinal plant: The ethnobiological and ethnomedicinal values of the Marind tribe in Merauke, Papua, Indonesia. Biodiversitas 17: 814-822. Biological resources around neighborhood play important roles in the cultural development of the surrounding communities, including the use of plants. Wati (kava, Piper methysticum) is one of the species that has long been used as a traditional medicine and cultivated by Marind tribal community in the lowlands of Merauke, Papua. The aim of this study is to examine the use and domestication of wati plant by Marind tribe in Papua.Results of the study showed that wati plant has long been used by the Marind tribal community as a medicinal plant with high customary value. Each customary event includes wati plant as a complementary requirement for legitimate activities by the Marind tribe. It is the importance of customary values that led the domestication of wati plant done since 60 years ago on a small scale to eventually develop into plant called as â€œthe Marind peopleâ€™s goldâ€. Results of the observation showed that 93.8% of the Marind people have largely recognized wati plant, while 53.3% of the immigrant communities from outside the area recognized it, but only 33.3% knew about its utilization. Although not all indigenous elders cultivate it, they recognize, utilize, and understand the rules of using wati plant in traditional events and as traditional medicine. As traditional medicine, the parts used by Marind people use root (100.0%), stem (96.6%), and leaves (89.7%). For customary events, the most important parts are the whole plant (100.0%), stem (100.0%), leaves (98.3%) and roots (93.1%). Their children even recognize it and know its benefits, but most of them 31.25% only utilize it but are prohibited from participating in its preparation (0.0%). The domestication of this plant is quite unique because it is closed to the public and is still done by a conventional method.